Stunting Prevention Interventions in Fulfilling Nutrition in Toddlers - Rezkillah, Albrina Roza; Surjoputro, Antono; Sriatmi, Ayun (LPPM Universitas Prima Nusantara Bukittinggi, 2023)
Background: Malnutrition especially during the critical period of the first 1000 days of life, will affect the growth and development of children, especially brain development, thus increasing the likelihood of suffering from chronic diseases in adulthood. The World Health Organization has set targets for nutritional status development, one of which aims to reduce the number of stunted children under the age of five by 40% by 2025.Purpose : To provide an overview of stunting prevention interventions in fulfilling nutrition in toddlers.Methods: This research design uses Scoping Review and article search and selection is based on the PRISMA method.Results: Search results on the ProQuest, Science Direct, and Scopus. Obtained as many as 238 articles that match the keywords searched. After screening according to the inclusion and exclusion criteria, 7 articles were selected to be included in this study, which are stunting prevention interventions in fulfilling nutrition in toddlers with lipid-based nutrient supplements (LNS), animal protein source complementary foods, complementary feeding of breast milk, combination of fish oil supplementation, provision of nutritious biscuits, and feeding containing hibiscus sabrida.Conclusion: Intervention of Stunting Prevention in the Fulfillment of Nutrition in toddlers can improve stunting prevention and increase linear growth in toddlers.